Internalisasi Nilai Moderasi Beragama dalam Living Fikih di Pesantren - Mohammad Lukman Chakim; Yasin Nurfalah (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2026)
This research aims to explain the process of internalizing the values of religious moderation within the pesantren educational system and how these values are manifested in the practice of living fiqh. This study employs a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation, and analyzed using a descriptive-analytical method to uncover patterns of internalizing moderation values in students' religious practices. The findings reveal that the internalization of religious moderation values at Pesantren Al-Falah Ploso occurs through the integration of three main strategies: a structured fiqh curriculum, fiqh deliberation (musyawarah fikih), and the chain of scholarly transmission. These three elements complement one another in shaping the students' understanding, experience, and religious attitudes. This internalization results in a moderate practice of living fiqh, reflected in mutual respect, moderation in adhering to legal schools (madhhab), and the ability to understand fiqh contextually. This indicates that religious moderation does not remain merely at the conceptual level but has been realized in students' actual behavior. Thus, moderate living fiqh becomes an important means of actualizing the values of religious moderation, where fiqh is understood not only as a normative text but also as lived in socio-religious practices.